Albinism in a raccoon Procyon lotor from Mexico - Rafael Flores-Peredo; Beatriz Bolívar-Cimé; Isac Mella-Méndez (Mammalogy Notes, 2021)
Albinism is defined as the complete absence of pigment in skin, hair, and eyes directly caused by a hereditary disorder in the production of melanin. This genetic abnormality is usually attributed to environmental factors such as low quality of habitat and inbreeding. In this note, we recorded a case of partial albinism in a raccoon (Procyon lotor) captured by poachers in the area known as Barranca de Matlacobatl, Municipality of Teocelo, Veracruz, Mexico. The specimen was recovered by the civil association Pro-Vida Silvestre Teocelotl and sheltered for a week under medical care. This is the second record in Mexico of a wild albino raccoon. Specifically, it was recorded particularly for a neotropical region of the center of the state of Veracruz, Mexico.